Improving the Reading Ability of Students Using the Cooperative Integrated Reading and Composition (CIRC) Method in Class IV SDN 3 Cilangkap - Ratnasari, Heni; Nurani, Riga Zahara; Febriani, Winarti Dwi (Social, Humanities, and Educational Studies (SHES): Conference Series, 2021)
This study aims to improve students' reading comprehension skills by using the Cooperative Integrated Reading and Composition (CIRC) method. This research method was conducted in 3 cycles using a classroom action research design belonging to Kemmis and Mc Taggart. In implementing this research, the steps of the Cooperative Integrated Reading and Composition (CIRC) method are used, which are divided into three stages, namely the opening activity, the core activity, and the closing activity. The results of the research in the first cycle obtained an average value of 78.6 with the percentage of students who had completed 70% and those who had not completed were 30%. Furthermore, in the second cycle an average score of 85.5 was obtained with the percentage of students who had completed 90% and those who had not completed were 10%. Meanwhile, in cycle III, an average score of 89.8 was obtained with the percentage of students who completed 100%. The results obtained, namely the Cooperative Integrated Reading And Composition (CIRC) method can improve reading comprehension skills of fourth grade students of SDN 3 Cilangkap, Tasikmalaya Regency.